2006
DOI: 10.1111/j.1365-2796.2006.01722.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of pro‐atrial natriuretic peptide in lower respiratory tract infections

Abstract: Abstract. Mü ller B, Sü ess E, Schuetz P, Mü ller C,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 49 publications
7
39
1
1
Order By: Relevance
“…Based on several clinical observational studies, circulating proADM and proANP have lately emerged as useful prognostic tools regarding all-cause mortality, ICU Brought to you by | Universitaetsbibliothek Basel Authenticated Download Date | 10/9/17 4:13 PM admission, severity of illness and disease-specific complications in CAP [9,6,25,[31][32][33]. The present analysis expands these findings by demonstrating a relevant correlation between high proADM and proANP levels and future decline in QoL in CAP patients.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Based on several clinical observational studies, circulating proADM and proANP have lately emerged as useful prognostic tools regarding all-cause mortality, ICU Brought to you by | Universitaetsbibliothek Basel Authenticated Download Date | 10/9/17 4:13 PM admission, severity of illness and disease-specific complications in CAP [9,6,25,[31][32][33]. The present analysis expands these findings by demonstrating a relevant correlation between high proADM and proANP levels and future decline in QoL in CAP patients.…”
Section: Discussionsupporting
confidence: 67%
“…In addition to clinical risk scores, such as the pneumonia severity index (PSI) [13], several inflammatory and/or cardiovascular blood biomarkers such as white blood cells (WBC), C-reactive protein (CRP), procalcitonin (PCT), pro-adrenomedullin (proADM), as well as pro-atrial natriuretic peptide (proANP) have been found helpful for risk prediction [6,[14][15][16][17][18][19][20]. Particularly, proADM [9,6,[21][22][23][24][25][26][27][28][29][30], proANP [9,6,25,[31][32][33] and PCT [10,22,25,31,[34][35][36] have been associated with risk for shortand long-term all-cause mortality as well as other adverse outcomes, such as severity of illness, admission to the intensive care unit (ICU), and disease-specific complications. Yet, there is insufficient evidence whether these clinical parameters and blood biomarkers are also helpful in predicting more subjective QoL outcomes: mens sana in corpore sano?…”
Section: Introductionmentioning
confidence: 99%
“…In CAP, the MR-pro-ANP level may mirror both the inflammatory cytokine response, correlated with the severity of pneumonia, as well as the presence of disease-relevant comorbidities, namely heart failure and renal dysfunction [110][111][112][113]. Therefore, the current authors investigated MR-pro-ANP levels in a well-defined cohort of 545 consecutive patients with LRTI, in order to evaluate its prognostic use for the severity of disease and outcome; this study had two main findings [101]. First, plasma MR-pro-ANP levels were increased in LRTI, with the highest levels in CAP.…”
Section: Biomarkers For the Prognostic Assessment Of Capmentioning
confidence: 99%
“…N-terminal proANP has shown to be of prognostic relevance in cardiovascular disease and myocardial infarction [11]. Furthermore, a significant difference in proANP levels between survivors and nonsurvivors has been assessed in respiratory tract infections including pneumonia, sepsis and VAP [12][13][14][15].…”
mentioning
confidence: 99%